(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This text discusses the implementation of the new curriculum of the Dance Degree Course at the Federal University of Santa Maria (UFSM). Developed between 2017 and 2019, the curricular reform aimed to meet the current legislation regarding ethnic-racial, gender, and inclusion issues. The new political-pedagogical project came into effect in 2020, with a perspective of multidiversity, multiculturalism, and decoloniality. It is considered that, based on the advances made, a paradigmatic change is still necessary: ongoing teacher training that caters to the change in the profile of students entering the university due to quota policies and the Unified Selection System (Sisu).